Peasant movements in the Centro Livestock Society (1910-1950) - Rénique, Gerardo (1978)
In this article we will try to analyze the struggles and peasant movements that occurred on the farms of the Sociedad Ganadera del Centro, in the context of the changes that occurred in its productive structure, originated in the variations of the wool economy in the high-Andean grasslands of the Andes. Centrals.